Enhanced heat transfer in rectangular duct with punched winglets - Promvonge, Pongjet; Skullong, Sompol (My University, 2020)
Thermal performance of a heat exchanger duct with punched winglets (PWs) mounted on the upper duct wall has been examined for Reynolds number (Re) ranging from 4100 to 25,500. In the present experiment, two types of PWs: punched delta- and elliptical-winglets (P-DW and P-EW) with four punched-hole sizes were tested at a fixed attack angle, optimal relative pitch and height. Also, data of solid delta- and elliptical-winglets (DW and EW) were included for comparison. The investigation has shown that the P-DW yields higher thermal-performance enhancement factor (η) than the P-EW. Although the solid DW and EW with no punch have the highest heat transfer and friction loss, the PWs yield better η than the solid ones. For PWs, the P-DW with smaller hole size has the peak heat transfer and friction loss around 5.7 and 40 times over the smooth duct, respectively but the optimum η of 2.17 is seen for the one with a certain hole size. The PWs provide η at about 5%–8% above the solid winglets.
Keywords: Flow resistance; Heat exchanger; Thermal-performance enhancement factor; Vortex generator; Winglet